Investigation of deformation behaviour during compression of miniature specimens using piezo-actuated micro-press - Madathuppalayam Chenniappan Kapil Raja (2016)
Miniaturization of metal forming process to micro forming level, which involves products with two dimensions smaller than 1 mm, gives rise to significant processing challenges. These challenges include added difficulty of material handling and process control, as well as changes in material and process behaviours with changing size, called the size effects. These size effects create problems such as process scatter and the incongruence while applying the knowledge from conventional size metal forming to micro forming. In previous work, a piezo-electric actuated micro compression machine was developed in-house with the objective of enabling higher freedom in movement control and better accuracy for micro forming studies than typical off-the-shelf mechanical presses. This study aims to examine the effects of strain rate and work piece size on the flow stress of commercially pure Aluminium. Commercially pure Al is selected in this study as there is high demand for this material for consumer electronics. The micro compression study showed increasing flow stress with decreasing sample size. The effects of strain rate and size on the resulting microstructures are also presented.